Infection with Helicobacter Pylori and The Risk of Iron Deficiency Anemia - Momna Arif, Mudassar Ashraf, Sadia Shah, Samaria Rashid, Saleem Ahmed Bhutto, Syed Irfan Raza Arif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Helicobacter pylori (H. pylori) is a well-known gastrointestinal pathogen implicated in various disorders, including peptic ulcers, gastritis, and gastric cancer. Recent studies have also suggested a possible relationship between H. pylori infection and iron deficiency anemia (IDA). This study aims to explore the association between H. pylori infection and the development of iron deficiency anemia in 150 patients. Methods: A prospective cohort study was conducted in 150 patients presenting to a Allama Iqbal Medical College, Jinnah Hospital Lahore with symptoms of anemia and dyspepsia. Patients were evaluated for H. pylori infection using the stool antigen test and for IDA by assessing hemoglobin, serum ferritin, and other iron studies. Demographic details, clinical findings, and comorbid conditions were recorded. Statistical analysis was performed using SPSS software. Results: Among the 150 patients, 90 (60%) were positive for H. pylori infection. The majority of H. pylori-positive patients (70%) were found to have moderate to severe iron deficiency anemia. Serum ferritin and hemoglobin levels were significantly lower in H. pylori infected individuals compared to those without infection (p<0.05). Conclusion: The study shows a significant association between H. pylori infection and iron deficiency anemia. These findings suggest that early diagnosis and treatment of H. pylori could reduce the risk of IDA, especially in regions with a high prevalence of the infection. Keywords: Helicobacter pylori, Iron deficiency anemia, Gastritis, Peptic ulcers, Serum ferritin, Hemoglobin levels, Risk factors